Velocity study of unmanned surface vehicle (USV) for depth measurement using numerical simulation - Zahari N.M.; Ismail I.N.; Nashrudin M.N.; Khamarudin H.F.; Zawawi M.H.; Aziz N.A.; Nurhikmah F.; Abas A. (American Institute of Physics, 2025)
It is necessary to perform an evaluation of boat performance for the boat safety of a self-developed unmanned surface vehicle (USV) boat to perform an in-situ depth measurement remotely. This paper investigates the water flow around the boat by using numerical simulation. A steady flow of water around the boat is successfully simulated using the finite volume method (FVM). Results shows that that the water flow is steady and smooth along the surface of the boat without any disturbances that may affect the boat performance and drag force also is low for this USV boat. ? 2024 Author(s).